2013
DOI: 10.3928/01484834-20130819-08
|View full text |Cite
|
Sign up to set email alerts
|

Early Indicators of NCLEX-RN Performance

Abstract: Health Education Systems Incorporated (HESI(™)) test results, course grades, and National Council Licensure Examination-Registered Nurse (NCLEX-RN(®)) outcomes of students in an associate degree nursing program at a midwestern public university were investigated. Statistical analysis revealed that introductory Fundamentals HESI test scores, more than either comprehensive HESI Exit Exam scores or other specialty HESI test scores, significantly predicted NCLEX-RN outcomes in this study (p < 0.05), while controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Similarly, HESI scores of adult health and family health were significant predictors for NCLEX-RN success, and this is in line with previous studies results. [13,30] Among other HESI exam scores, EXIT was found to be a significant predictor of NCLEX-RN success. This is also consistent with previous studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, HESI scores of adult health and family health were significant predictors for NCLEX-RN success, and this is in line with previous studies results. [13,30] Among other HESI exam scores, EXIT was found to be a significant predictor of NCLEX-RN success. This is also consistent with previous studies.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with previous a study's finding. [30] The moderation effect of gender on the association between course grades/HESI of family health and NCLEX-RN success was not statistically significant, indicating family health course grades and HESI scores were significant factors related to NCLEX-RN success regardless of gender. Considering the findings of this study, support should be given to both male and female students to improve their knowledge level and clinical skills specifically for family health and child health nursing courses.…”
Section: Discussionmentioning
confidence: 93%
“…2,3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The predictive accuracy of the E2 has been studied regularly since 1999. 2,3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The predictive accuracy of the E2 has been studied regularly since 1999.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results differed in that Vandenhouten 5 found that RNCP scores among 296 predominantly white female students were significant predictors of NCLEX-RN success, whereas Yates 30 did not find that same outcome in a large group (n = 298) of racially diverse nursing students. Academic variables include high school rank, high school GPA, 32,33 ACT and SAT scores, [32][33][34][35] critical thinking test scores, 36 National League for Nursing Achievement Test scores, 31-33 ATI Test of Essential Academic Skills and nursing Content Mastery examination scores, 31 HESI specialty examination scores, 22 nursing theory course grades, 22,[32][33][34][35] and nursing program GPA. Unlike the studies by Alameida and colleagues 4 and Ukpabi, 31 the studies by Vandenhouten 5 and Yates 30 were conducted among community college students enrolled in associate nursing degree programs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation